PENGGUNAAN TEKNIK MODELING TERHADAP PERENCANAAN KARIR SISWA - Sofwan Adiputra, author (JURNAL FOKUS KONSELING, 2015)
This study aimed to lead stdents in order to they are able to plan career by comprehending their interest and potential toward a task at the first grade of senior high school Yasmida Ambarawa. This study employed quassi-experimental method with the non-equivalent control group. Purposive sampling technique was used to determine the simple. This study used non-parametric statistic analysis with level test (uji jenjang) signed ranks test and smirnov-kolmogorof method for dable sample group. Based on the finding, it can be concluded that career planning which applied earlier will develop responsibility attitude for students so they are able to develop their abaility as maximum as possible, and not to do deviation toward development duty. The use of modeling technique was effective to improve students career planning at the first grade of senior high school Yasmida Ambarawa.Keywords: Group Counseling, Modeling Techniques, Career PlanningÂ